2022
DOI: 10.1111/jce.15735
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic measures of repolarization heterogeneity are not predictive for Torsades de Pointes among undifferentiated patients with prolonged QTc: A case control study

Abstract: Introduction Torsades de Pointes (TdP) is a potentially lethal polymorphic ventricular tachydysrhythmia associated with and caused by prolonged myocardial repolarization. However, prediction of TdP is challenging. We sought to determine if electrocardiographic myocardial repolarization heterogeneity is necessary and predictive of TdP. Methods We performed a case control study of TdP at a large urban hospital. We identified cases based on a hospital center electrocardiogram (ECG) database search for tracings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 23 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Lessons to be learned from the present study . The important take‐home message from the present study 8 is that once a definitely long QT is identified, telling apart patients who will develop torsade‐de‐pointes, from those who will not, is difficult. This is in agreement with observations made in the large azimilide‐studies alluded before 12 : Although the risk of torsade‐de‐pointes increased significantly once the QTc increased above 500 ms and augmented sharply once the QTc reached 580 ms, the majority of patients with torsade had QTc below these values whereas a significant proportion of patients without torsade developed QTc values above those limits 12 …”
Section: Figurementioning
confidence: 92%
See 4 more Smart Citations
“…Lessons to be learned from the present study . The important take‐home message from the present study 8 is that once a definitely long QT is identified, telling apart patients who will develop torsade‐de‐pointes, from those who will not, is difficult. This is in agreement with observations made in the large azimilide‐studies alluded before 12 : Although the risk of torsade‐de‐pointes increased significantly once the QTc increased above 500 ms and augmented sharply once the QTc reached 580 ms, the majority of patients with torsade had QTc below these values whereas a significant proportion of patients without torsade developed QTc values above those limits 12 …”
Section: Figurementioning
confidence: 92%
“…The authors then focused on ECG parameters, like T peak – T end , the interval from the peak to the end of the T‐wave (an accepted surrogate from increased dispersion of repolarization), 11 focusing also on T‐wave morphology. None of these ECG parameters were useful for telling apart patients with torsade‐de‐pointes from patients with comparable, yet uneventful, severe QT‐prolongation 8 . The number of patients studied was small (75 patients vs. 150 controls); accordingly, the absence of predictive value for the ECG parameters tested, may reflect insufficient statistical power.…”
Section: Figurementioning
confidence: 95%
See 3 more Smart Citations